The body is not an apology : the power of radical self-love - Taylor, Sonya Renee (Berrett-Koehler Publishers, Inc., 2021)
Humans are a varied and divergent bunch with all manner of beliefs, morals, and bodies. Systems of oppression thrive off our inability to make peace with difference and injure the relationship we have with our own bodies. The Body Is Not an Apology offers radical self-love as the balm to heal the wounds inflicted by these violent systems. World-renowned activist and poet Sonya Renee Taylor invites us to reconnect with the radical origins of our minds and bodies and celebrate our collective, enduring strength. As we awaken to our own indoctrinated body shame, we feel inspired to awaken others and to interrupt the systems that perpetuate body shame and oppression against all bodies. When we act from this truth on a global scale, we usher in the transformative opportunity of radical self-love, which is the opportunity for a more just, equitable, and compassionate world--for us all. This second edition includes stories from Taylor's travels around the world combating body terrorism and shines a light on the path toward liberation guided by love. In a brand new final chapter, she offers specific tools, actions, and resources for confronting racism, sexism, ableism, homophobia, and transphobia. And she provides a case study showing how radical self-love not only dismantles shame and self-loathing in us but has the power to dismantle entire systems of injustice. Together with the accompanying workbook, Your Body Is Not an Apology, Taylor brings the practice of radical self-love to life.